Tabriz (Nordwest-Iran) und der Tabrizer Bazar - Schweizer, Günther (ERDKUNDE, 1972)
The town of Tabriz, in North West Iran, was the capital of a gigantic empire during the Mongol Era and, even in the last century, was the most important commercial city in Iran but has since suffered a strong decline in its importance. Despite repeated attempts at modernisation it is possible to distinguish a strong surviving conservative, traditional element in the urban scene and in economic life. Even today the traditional bazaar forms the real heart of the town. Comparison of the current buildings with earlier reports and with a town plan of 1880 shows that the bazaar was newly laid out in the years 1840 to 1860. Since this time the buildings of the bazaar have remained practically unaltered. In contrast the distribution of branches of trade in the bazaar, the position of which was investigated in a detailed mapping exercise in 1969 (Map 5) has shown a strong change. This is shown by older reports and by analysis of the names of individual bazaar passages and caravanserais. The functional restructuring of the Tabriz bazaar is not only limited to a new distribution of the individual branches but also embraces changes in the socio-geographical structure. The re-location of urban trade from the bazaar to the modern shopping quarter has, however, not proceeded very strongly in Tabriz. The bazaar has maintained its importance as a shopping centre far more than in other major oriental cities. Nevertheless, it can be assumed that Tabriz will overcome her backwardness in development in the next few years, under western influence, since when current plans are realised she will be developed into one of Iran’s largest industrial centres.